Methanol oxidation catalyst and preparation method thereof

By using nano-titanium ruthenium oxide composite materials as catalyst matrix and forming a nano-nickel cobalt manganese metal layer through surface modification and multi-layer nano-metal deposition technology, the problem of unstable activity of existing catalysts under high temperature and high pressure conditions is solved, and the problem of instability of existing catalysts is achieved. Efficient methanol oxidation reaction.

CN119425724AActive Publication Date: 2025-02-14LIAONING DEHUI TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411334846.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing methanol oxidation catalysts have unstable catalytic activity under high temperature and high pressure conditions and have low reaction efficiency, making it difficult to meet the efficient needs of industrial production.

Method used

The nanotitanium ruthenium oxide composite material prepared by titanium dioxide and ruthenium oxide is used as the catalyst matrix. Through surface modification and multi-layer nanometal deposition technology, a nano nickel cobalt manganese metal layer is formed to improve the surfactivity and thermal stability of the catalyst.

Benefits of technology

The catalytic efficiency and stability of methanol oxidation reaction are significantly improved, the excellent performance of catalytic activity under high temperature and high pressure conditions is maintained, the generation of by-products is reduced, and the yield and purity are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a methanol oxidation catalyst and a preparation method thereof, and relates to the field of catalysts. The nano titanium ruthenium oxide prepared by a low-temperature hydrothermal method is used as the carrier, the titanium ruthenium oxide crystal phase is of an anatase structure, the nano titanium ruthenium oxide crystal phase and the deposited nickel cobalt manganese metal form a composite structure, a synergistic effect is achieved, and the catalytic performance on methanol is improved. Titanium oxide ruthenium metal is pretreated and then soaked in a self-made water-phase nanometer nickel solution to form a first nanometer nickel metal layer, then surface modification is conducted through a silane coupling agent, then the first nanometer nickel metal layer is placed in a water-phase nanometer cobalt solution, the steps are repeated, a second nanometer cobalt particle layer and a third nanometer manganese particle layer are deposited, and the nanometer nickel metal layer is obtained. And finally, carrying out reduction treatment to obtain the methanol oxidation catalyst with the nano nickel-cobalt-manganese metal layer deposited by taking the titanium ruthenium oxide as the carrier. The catalyst prepared by the invention and methanol generate efficient chain exothermic reaction, the catalytic oxidation is complete, and the catalytic efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a methanol oxidation catalyst and a preparation method thereof. Background Art

[0002] Methanol, also known as hydroxymethane, wood alcohol or wood spirits, is an organic compound and the simplest saturated monohydric alcohol. Its chemical formula is CH3OH or CH4O, its molecular weight is 32.04, and its boiling point is 64.7℃. Methanol is colorless, volatile and flammable.

[0003] Methanol oxidation is a chemical reaction between methanol and oxygen (or other oxidants) in the presence of a catalyst. This reaction plays an important role in many fields:

[0004] Production of formaldehyde: Methanol oxidation is the main method for producing formaldehyde. Formaldehyde is an important chemical raw material and is widely used in adhesives, coatings, molding compounds and other industries. Formaldehyde can be efficiently produced through methanol air oxidation. In this process, methanol reacts with oxygen under the action of a catalyst to produce formaldehyde and water.

[0005] Energy field: In the field of fuel cells, methanol oxidation is also one of the core reactions of methanol fuel cells (DMFC). DMFC is a device that directly converts the chemical energy of methanol into electrical energy, with the advantages of high energy density and environmental protection. In DMFC, methanol undergoes an oxidation reaction under the action of the anode catalyst to produce carbon dioxide, protons and electrons, of which protons are transmitted to the cathode through the electrolyte membrane and react with the oxygen at the cathode to produce water, while electrons are transmitted through the external circuit to form an electric current.

[0006] Organic synthesis: Methanol oxidation can also be used in the field of organic synthesis. Aldehydes, ketones and other organic compounds can be generated through oxidation reactions. These compounds are widely used in the pharmaceutical, pesticide, dye and other industries.

[0007] The research on methanol oxidation catalyst helps to optimize the production process and improve production efficiency. By selecting the appropriate catalyst and reaction conditions, efficient conversion of methanol can be achieved, the yield and purity of the target product can be increased, and the generation of by-products can be reduced, thereby saving raw materials and reducing waste emissions. Summary of the invention

[0008] The object of the present invention is to provide a methanol oxidation catalyst and a preparation method thereof to solve the problems existing in the prior art.

[0009] In order to solve the above problems, the present invention provides the following technical solution: a method for preparing a methanol oxidation catalyst, comprising the following preparation steps:

[0010] (1) Add ruthenium salt to a container, add deionized water to dissolve, then pour into a cup, add hydrogen peroxide while stirring, stir evenly, and cool in an ice bath;

[0011] (2) adding the metallic titanium compound to the solution, stirring evenly, then adding urea, stirring continuously, and cooling to room temperature;

[0012] (3) placing the solution obtained in step (2) in a pressure cooker to carry out a high temperature and high pressure reaction, washing with water and centrifuging after the reaction is complete, and then vacuum drying to obtain a nano titanium ruthenium oxide carrier;

[0013] (4) washing the nano-titanium ruthenium oxide carrier obtained in step (3), placing it in an oven, drying it under an inert gas, then adding a surface modifier to soak it, letting it stand, taking it out after the reaction is complete, washing it with deionized water and alcohol, drying it in an oven under an inert gas, cooling it to room temperature, placing it in a test tube filled with an inert gas, and refrigerating it in a refrigerator;

[0014] (5) taking an aqueous solution of nano-nickel particles, placing the support after surface treatment in step (4) in the solution for immersion, taking it out for washing, and drying it under inert gas, thereby completing the deposition of a single layer of nano-nickel on the titanium ruthenium oxide support;

[0015] (6) The titanium ruthenium oxide support on which the nano-nickel metal is deposited obtained in step (5) is immersed in a surface modifier, and after being wetted, is placed in an oven and dried under an inert gas to complete the surface modification.

[0016] (7) taking a nano-cobalt particle aqueous solution, placing the titanium ruthenium oxide support obtained in step (6) into the solution for immersion, taking it out for washing, and drying it under an inert gas, thereby completing the double-layer nano-nickel-cobalt deposition on the titanium ruthenium oxide support;

[0017] (8) The ruthenium oxide support on which the double-layer nano-nickel and cobalt are deposited obtained in step (7) is immersed in a surface modifier, wetted, and then placed in an oven to dry under an inert gas to complete the surface modification.

[0018] (9) taking an aqueous solution of nano-manganese particles, placing the titanium ruthenium oxide support obtained in step (8) in it for immersion, taking it out for washing, and drying it under inert gas, thereby completing the deposition of three layers of nano-nickel, cobalt and manganese on the titanium ruthenium oxide support;

[0019] (10) placing the titanium ruthenium oxide support on which three layers of nano-nickel, cobalt and manganese metals are deposited obtained in step (9) in a sealed furnace, introducing a mixed gas, and heating the furnace for heat treatment to obtain a titanium ruthenium oxide methanol oxidation catalyst carrying nano-nickel, cobalt and manganese metals after the reaction is complete;

[0020] The surface modifier in step (4) is a methanol solution containing a titanium alkyl compound with a concentration of 1% to 5%; the surface modifier in steps (6) and (8) is a 3-aminopropyltriethoxysilane-methanol solution with a concentration of 1% to 5%.

[0021] Furthermore, the ruthenium salt is ruthenium chloride; the metal titanium compound is tetraethyl titanium

[0022] Furthermore, the mass concentration of hydrogen peroxide in step (1) is 30% to 40%; and the mass concentration of urea in step (2) is 0.3 to 0.7M.

[0023] Furthermore, the ice bath temperature in step (1) is 0-5°C; the oven temperature in step (3) is 200-300°C, the time is 2-6 hours, and the heating rate is 5-15°C / min; the centrifugal speed in step (3) is 5000-6000 r / min.

[0024] Furthermore, the inert gas is nitrogen; the standing time of steps (5), (7) and (9) is 6 to 18 hours; the drying temperature is 200 to 300° C., and the drying time is 1 to 3 hours.

[0025] Furthermore, the mixed gas in step (10) is 5% hydrogen and 95% argon; the reaction temperature is 550-650°C, the heating rate is 5-15°C / min, and the reaction time is 4-8h.

[0026] Furthermore, the aqueous nano nickel solution is prepared by the following steps: adding a nickel chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding a sodium borohydride aqueous solution, continuously stirring, cooling to room temperature, and obtaining an aqueous nano nickel particle solution; the molar concentration of the nickel chloride is 0.5 to 5.0 mM, and the molar concentration of the sodium borohydride is 0.5 to 5.0 mM.

[0027] Furthermore, the aqueous nano-cobalt solution is prepared by the following steps: adding a cobalt chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding a sodium borohydride aqueous solution, continuously stirring, cooling to room temperature, and obtaining an aqueous nano-cobalt particle solution; the cobalt chloride concentration is 0.5 to 5.0 mM, and the sodium borohydride concentration is 0.5 to 5.0 mM.

[0028] Furthermore, the aqueous nano-manganese solution is prepared by the following steps: the aqueous nano-manganese solution is prepared by the following steps: adding an aqueous manganese chloride solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding an aqueous sodium borohydride solution, continuously stirring, and cooling to room temperature to obtain an aqueous nano-manganese particle solution; the manganese chloride concentration is 0.5 to 5.0 mM, and the sodium borohydride concentration is 0.5 to 5.0 mM.

[0029] Furthermore, a methanol oxidation catalyst is provided, and the catalyst is prepared according to the method.

[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0031] The present invention uses a titanium dioxide ruthenium oxide composite material prepared from titanium dioxide and ruthenium oxide as a catalyst matrix. The crystal phase of titanium dioxide ruthenium oxide is anatase structure, has more surface hydroxyls, has good catalytic activity, and has strong thermal stability of the anatase structure, and can maintain excellent catalytic activity in the high-temperature exothermic reaction of methanol oxidation; and the titanium dioxide ruthenium carrier provides more active sites, which is convenient for the deposition and attachment of nano-metal particles, so that they are better dispersed, increase the effective contact area of ​​the methanol oxidation reaction, and improve the catalytic efficiency. The present invention uses a silane coupling agent to perform surface treatment on the titanium dioxide ruthenium carrier before deposition, and chemically reacts with the surface hydroxyls of titanium dioxide ruthenium oxide to form a strong chemical bond, which can enhance the adhesion between the subsequently deposited metal nanoparticles and the carrier; and improves the stability of the catalyst at high temperature, reduces the phase change and structural change during the heat treatment process; the formation of the modified layer changes the microenvironment of the nanoparticles, helps the metal nanoparticles reduce aggregation, disperse evenly, and improves their reaction activity and catalytic efficiency.

[0032] The invention uses self-made aqueous nanoparticles to impregnate the titanium ruthenium oxide carrier after surface treatment, uses a silane coupling agent to perform surface modification after each nanometal layer is formed, and then deposits the next layer of metal particles to form three nanometal layers of nickel, cobalt and manganese on the surface of the titanium ruthenium oxide; controls the deposition sequence, deposits nano nickel particles first, and the nickel particles and the titanium ruthenium oxide carrier have a strong interface effect, which is conducive to the subsequent deposition of metal particles to form a composite structure to improve the catalytic performance, and the nano nickel particles and the carrier have good electronic matching, which improves the catalytic activity, and the subsequent deposition of nano cobalt particles further adjusts the electron density and distribution, prevents element aggregation, controls the dispersion, generates more active sites, optimizes the catalytic performance, and finally deposits the nano nickel particles. The nano-manganese particles form a core-shell structure on the surface of the cobalt particles, providing more interfacial active sites, and forming a protective layer to improve the stability of the catalyst under high temperature and high pressure, and reduce the loss and aggregation of metal particles; the use of coupling agents, the introduction of silanol groups to form covalent bonds with the hydroxyl groups on the surface of the substrate, improves adhesion, and forms an organic protective layer on the surface of the carrier, which helps to control the nucleation and growth of metal particles and prevent the excessive aggregation of metal nanoparticles during the next impregnation process, thereby helping to maintain or improve the dispersion of metal particles, prevent particle aggregation, thereby increasing the effective active surface area of ​​the catalyst and improving the catalytic efficiency; and the introduction of amino groups after modification provides more active sites, which helps the subsequent deposition of particles.

[0033] The present invention utilizes methanol and three-layer nano-metal particles, and through a special multiple redox reaction technology, produces a transition substance gas in the middle, which prompts methanol to undergo a complex chemical reaction at high temperature. There are many transition substances in the reaction, and the most important one is the generation of proton hydrogen, which will induce a new round of chemical reactions, making the reaction cycle endless, but the final products are still water and carbon dioxide. This redox reaction makes the methanol oxidation exothermic reaction more complete, improves the reaction efficiency, and forms a high-efficiency thermal reaction structure. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] (1) adding 10 parts of a 2.5 mM nickel chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 10 parts of a 2.5 mM sodium borohydride aqueous solution, stirring continuously for 10 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nickel nanoparticle solution;

[0037] (2) adding 10 parts of a 2.5 mM aqueous solution of cobalt chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 10 parts of a 2.5 mM aqueous solution of sodium borohydride, stirring continuously for 10 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nano-cobalt particle solution;

[0038] (3) adding 10 parts of a 2.5 mM aqueous solution of manganese chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 10 parts of a 2.5 mM aqueous solution of sodium borohydride, stirring continuously for 10 minutes, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nano-manganese particle solution;

[0039] (4) Add 15 parts of ruthenium chloride to a container, add deionized water to dissolve, then pour into a Teflon cup, add 45 parts of 35% hydrogen peroxide while stirring, stir evenly, and cool in an ice bath to control the temperature to 2.5°C;

[0040] (5) adding 30 parts of tetraethyl titanium to the solution, stirring evenly, then adding 10 parts of 0.5 M urea, stirring continuously, and cooling to room temperature;

[0041] (6) placing the solution obtained in step (5) in a pressure cooker, and then placing it in an oven at 250° C., 25 MPa, for 4 h, with a heating rate of 10° C. / min. After the reaction is complete, washing and centrifuging are performed at a centrifuge speed of 5500 r / min, and then vacuum drying at 80° C. to obtain a nano-titanium ruthenium oxide carrier;

[0042] (7) Take 15 parts of the nano-titanium ruthenium oxide carrier obtained in step (6), wash it, and then place it in an oven under nitrogen at 250°C for drying, then add 50 parts of a 3% methanol solution containing a titanium alkyl compound to soak it, let it stand for 4 hours, take it out after the reaction is complete, wash it with deionized water and alcohol, dry it in an oven at 250°C under nitrogen for 1 hour, cool it to room temperature, put it in a test tube filled with nitrogen, and put it in a refrigerator for refrigeration;

[0043] (8) Take 5 parts of the aqueous solution of nano-nickel particles prepared in step (1), add 50 parts of deionized water to dilute, place the support after surface treatment in step (7) in the solution and soak for 12 hours, take out and wash, and dry at 250° C. under nitrogen for 2 hours, thereby completing the deposition of a single layer of nano-nickel on the titanium ruthenium oxide support;

[0044] (9) The ruthenium oxide support on which the nano-nickel metal is deposited obtained in step (8) is immersed in 50 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, and after being wetted, is placed in an oven and dried at 250° C. under nitrogen to complete the surface modification;

[0045] (10) Take 5 parts of the aqueous solution of nano-cobalt particles prepared in step (2), add 50 parts of deionized water to dilute it, soak the titanium ruthenium oxide support obtained in step (9) for 12 hours, take it out for washing, and dry it at 250° C. under nitrogen for 2 hours, thereby completing the double-layer nano-nickel-cobalt deposition on the titanium ruthenium oxide support;

[0046] (11) The ruthenium oxide support on which the double-layer nano-nickel-cobalt metal is deposited obtained in step (10) is immersed in 50 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, and after being wetted, is placed in an oven and dried at 250° C. under nitrogen to complete the surface modification;

[0047] (12) Take 5 parts of the aqueous solution of nano-manganese particles prepared in step (3), add 50 parts of deionized water to dilute it, soak the titanium ruthenium oxide support obtained in step (10) for 12 hours, take it out for washing, and dry it at 250° C. under nitrogen for 2 hours, thereby completing the three-layer nano-nickel, cobalt and manganese deposition on the titanium ruthenium oxide support;

[0048] (13) The titanium ruthenium oxide carrier on which three layers of nano-nickel, cobalt and manganese metals are deposited obtained in step (12) is placed in a quartz U-shaped tube plugged with quartz wool, and a mixed gas of 5% hydrogen and 95% argon is introduced at 600°C with a heating rate of 10°C / min for 6 hours to obtain a titanium ruthenium oxide methanol oxidation catalyst on which nano-nickel, cobalt and manganese metals are deposited.

[0049] Example 2

[0050] (1) adding 15 parts of a 5 mM nickel chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 15 parts of a 5 mM sodium borohydride aqueous solution, stirring continuously for 20 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nickel nanoparticle solution;

[0051] (2) adding 15 parts of a 5 mM aqueous solution of cobalt chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 15 parts of a 5 mM aqueous solution of sodium borohydride, stirring continuously for 20 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nano-cobalt particle solution;

[0052] (3) adding 15 parts of a 5 mM aqueous solution of manganese chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 15 parts of a 5 mM aqueous solution of sodium borohydride, stirring continuously for 20 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nano-manganese particle solution;

[0053] (4) Add 25 parts of ruthenium chloride to a container, add deionized water to dissolve, then pour into a Teflon cup, add 60 parts of 35% hydrogen peroxide while stirring, stir evenly, and cool in an ice bath to control the temperature to 5°C;

[0054] (5) adding 50 parts of tetraethyl titanium to the solution, stirring evenly, then adding 15 parts of 0.7 M urea, stirring continuously, and cooling to room temperature;

[0055] (6) placing the solution obtained in step (5) in a pressure cooker, and then placing it in an oven at 300° C., 30 MPa, for 6 h, with a heating rate of 15° C. / min. After the reaction is complete, washing and centrifugation are performed at a centrifuge speed of 6000 r / min, and then vacuum drying at 100° C. to obtain a nano-titanium ruthenium oxide carrier;

[0056] (7) Take 25 parts of the nano-titanium ruthenium oxide carrier obtained in step (6), wash it, and then place it in an oven under nitrogen at 300°C for drying, then add 60 parts of a 3% methanol solution containing a titanium alkyl compound to soak it, let it stand for 6 hours, take it out after the reaction is complete, wash it with deionized water and alcohol, dry it in an oven at 300°C for 3 hours under nitrogen, cool it to room temperature, put it in a test tube filled with nitrogen, and put it in a refrigerator for refrigeration;

[0057] (8) Take 8 parts of the aqueous solution of nano-nickel particles prepared in step (1), add 60 parts of deionized water to dilute, place the support after surface treatment in step (7) in the solution and soak for 18 hours, take out and wash, and dry at 300° C. under nitrogen for 3 hours, thereby completing the deposition of a single layer of nano-nickel on the titanium ruthenium oxide support;

[0058] (9) The ruthenium oxide support on which the nano-nickel metal is deposited obtained in step (8) is immersed in 60 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, and after being wetted, is placed in an oven and dried at 300° C. under nitrogen to complete the surface modification;

[0059] (10) Take 8 parts of the aqueous solution of nano-cobalt particles prepared in step (2), add 60 parts of deionized water, soak the titanium ruthenium oxide support obtained in step (9) for 18 hours, take out and wash, and dry at 300° C. under nitrogen for 3 hours, thereby completing the double-layer nano-nickel-cobalt deposition on the titanium ruthenium oxide support;

[0060] (11) The ruthenium oxide support on which the double-layer nano-nickel-cobalt metal is deposited obtained in step (10) is immersed in 60 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, wetted, placed in an oven, and dried at 300° C. under nitrogen to complete the surface modification;

[0061] (12) Take 8 parts of the aqueous solution of nano-manganese particles prepared in step (3), add 60 parts of deionized water to dilute it, soak the titanium ruthenium oxide support obtained in step (10) for 18 hours, take it out for washing, and dry it at 300° C. under nitrogen for 3 hours, thereby completing the three-layer nano-nickel, cobalt and manganese deposition on the titanium ruthenium oxide support;

[0062] (13) The titanium ruthenium oxide carrier on which three layers of nano-nickel, cobalt and manganese metals are deposited obtained in step (12) is placed in a quartz U-shaped tube plugged with quartz wool, and a mixed gas of 5% hydrogen and 95% argon is introduced. The temperature is 650° C., the heating rate is 15° C. / min, and the reaction is carried out for 8 hours to obtain a titanium ruthenium oxide methanol oxidation catalyst on which nano-nickel, cobalt and manganese metals are deposited.

[0063] Example 3

[0064] (1) adding 5 parts of a 0.5 mM nickel chloride aqueous solution to a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 5 parts of a 0.5 mM sodium borohydride aqueous solution, stirring continuously for 5 min, waiting for the reaction to be complete, cooling to room temperature, and obtaining an aqueous nickel nanoparticle solution;

[0065] (2) adding 5 parts of a 0.5 mM aqueous solution of cobalt chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 5 parts of a 0.5 mM aqueous solution of sodium borohydride, stirring continuously for 5 minutes, waiting for the reaction to be complete, and cooling to room temperature to obtain an aqueous nano-cobalt particle solution;

[0066] (3) adding 5 parts of a 0.5 mM aqueous solution of manganese chloride to the container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding 5 parts of a 0.5 mM aqueous solution of sodium borohydride, stirring continuously for 5 minutes, waiting for the reaction to be complete, and cooling to room temperature to obtain an aqueous nano-manganese particle solution;

[0067] (4) Add 10 parts of ruthenium chloride to a container, add deionized water to dissolve, then pour into a Teflon cup, add 30 parts of 35% hydrogen peroxide while stirring, stir evenly, and cool in an ice bath to control the temperature to 0°C;

[0068] (5) adding 20 parts of tetraethyl titanium to the solution, stirring evenly, then adding 510 parts of 0.3 M urea, stirring continuously, and cooling to room temperature;

[0069] (6) placing the solution obtained in step (5) in a pressure cooker, and then placing it in an oven at 200° C. for 2 h at a heating rate of 5° C. / min. After the reaction is complete, washing and centrifugation are performed at a centrifuge speed of 5000 r / min, and then vacuum drying at 90° C. to obtain a nano-titanium ruthenium oxide carrier;

[0070] (7) Take 10 parts of the nano-titanium ruthenium oxide carrier obtained in step (6), wash it, and then place it in an oven under nitrogen at 200°C for drying, then add 40 parts of a 3% methanol solution containing a titanium alkyl compound to soak it, let it stand for 2 hours, take it out after the reaction is complete, wash it with deionized water and alcohol, dry it in an oven at 200°C under nitrogen for 1 hour, cool it to room temperature, put it in a test tube filled with nitrogen, and put it in a refrigerator for refrigeration;

[0071] (8) Take 3 parts of the aqueous solution of nano-nickel particles prepared in step (1), add 40 parts of deionized water to dilute, place the support after surface treatment in step (7) in the solution for 6 hours, take out and wash, and dry at 200° C. under nitrogen for 2 hours, thereby completing the deposition of a single layer of nano-nickel on the titanium ruthenium oxide support;

[0072] (9) The ruthenium oxide support on which the nano-metal nickel was deposited obtained in step (8) was immersed in 40 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, and after being wetted, was placed in an oven and dried at 200° C. under nitrogen to complete the surface modification;

[0073] (10) Take 3 parts of the aqueous solution of nano-cobalt particles prepared in step (2), add 40 parts of deionized water to dilute it, and soak the titanium ruthenium oxide support obtained in step (9) for 6 hours, take it out for washing, and dry it at 200° C. under nitrogen for 1 hour, thereby completing the double-layer nano-nickel-cobalt deposition on the titanium ruthenium oxide support;

[0074] (11) The ruthenium oxide support on which the double-layer nano-nickel-cobalt metal is deposited obtained in step (10) is immersed in 40 parts of a 3% 3-aminopropyltriethoxysilane-methanol solution, wetted, placed in an oven, and dried at 200° C. under nitrogen to complete the surface modification;

[0075] (12) Take 3 parts of the aqueous solution of nano-manganese particles prepared in step (3), add 40 parts of deionized water to dilute it, and soak the titanium ruthenium oxide support obtained in step (10) for 6 hours, take it out for washing, and dry it at 200° C. under nitrogen for 1 hour, thereby completing the three-layer nano-nickel, cobalt and manganese deposition on the titanium ruthenium oxide support;

[0076] (13) The titanium ruthenium oxide carrier on which three layers of nano-nickel, cobalt and manganese metals are deposited obtained in step (12) is placed in a quartz U-shaped tube plugged with quartz wool, and a mixed gas of 5% hydrogen and 95% argon is introduced. The temperature is 550° C., the heating rate is 5° C. / min, and the reaction is carried out for 4 hours to obtain a titanium ruthenium oxide methanol oxidation catalyst on which nano-nickel, cobalt and manganese metals are deposited.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that steps (4), (5) and (6) are deleted, and step (7) is changed to taking 10 parts of titanium dioxide and 5 parts of ruthenium oxide, washing them, and then placing them in an oven under nitrogen at 250°C for drying, then adding 50 parts of a 3% methanol solution containing a titanium alkyl compound to soak them, letting them stand for 4 hours, taking them out after the reaction is complete, washing them with deionized water and alcohol, drying them in an oven at 250°C under nitrogen for 1 hour, cooling them to room temperature, placing them in a test tube filled with nitrogen, and refrigerating them; the remaining steps are the same as those in Example 1.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 1 is that in step (7), step (7) is changed to taking 15 parts of the nano titanium ruthenium oxide carrier obtained in step (6), washing it, and then placing it in an oven under nitrogen at 250°C for drying. After cooling to room temperature, it is placed in a test tube filled with nitrogen and refrigerated in a refrigerator. The remaining steps are the same as in Example 1.

[0081] Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 1 is that steps (9) to (12) are changed to taking 5 parts of the aqueous solution of nano-cobalt particles prepared in step (2), adding 50 parts of deionized water to dilute, then soaking the carrier for deposition for 12 hours, taking it out, and drying it at 250°C under nitrogen, then taking 5 parts of the aqueous solution of nano-manganese particles prepared in step (3), adding 50 parts of deionized water to dilute, then placing the dried carrier in the soaking and deposition for 12 hours, taking it out, and drying it at 250°C under nitrogen.

[0083] Comparative Example 4

[0084] In Comparative Example 4, only the deposition order was changed to obtain a titanium ruthenium oxide metal catalyst deposited with three layers of nickel, manganese and cobalt nanometals. The deposition process was the same as that of Example 1.

[0085] Comparative Example 5

[0086] In Comparative Example 5, only the deposition order was changed to obtain a titanium ruthenium oxide metal catalyst deposited with three layers of manganese, nickel and cobalt nanometals. The deposition process was the same as that of Example 1.

[0087] Comparative Example 6

[0088] In Comparative Example 6, only the deposition order was changed to obtain a titanium ruthenium oxide metal catalyst deposited with three layers of nano-metals of manganese, cobalt and nickel. The deposition process was the same as that of Example 1.

[0089] Comparative Example 7

[0090] In Comparative Example 7, only the deposition order was changed to obtain a titanium ruthenium oxide metal catalyst deposited with three layers of cobalt, manganese and nickel nanometals. The deposition process was the same as that of Example 1.

[0091] Comparative Example 8

[0092] In Comparative Example 8, only the deposition order was changed to obtain a titanium ruthenium oxide metal catalyst deposited with three layers of cobalt, nickel and manganese nanometals. The deposition process was the same as that of Example 1.

[0093] Comparative Example 9

[0094] The difference between Comparative Example 9 and Example 1 is that step (3) is deleted, and step (12) is changed to taking 5 parts of a 0.5M / L nanosilver particle solution, adding 50 parts of deionized water to dilute it, and soaking the titanium ruthenium oxide support on which a double layer of nano-nickel cobalt metal is deposited obtained in step (10) for 12 hours, taking it out for washing, and drying it at 250°C under nitrogen for 2 hours, thereby completing the three-layer nano-nickel cobalt silver deposition on the titanium ruthenium oxide support; the remaining steps are the same as in Example 1.

[0095] Comparative Example 10

[0096] The difference between Comparative Example 10 and Example 1 is that step (3) is deleted, and step (12) is changed to taking 5 parts of a 0.5M / L nano-gold particle solution, adding 50 parts of deionized water to dilute it, and soaking the titanium ruthenium oxide support on which a double layer of nano-nickel cobalt metal is deposited obtained in step (10) for 12 hours, taking it out for washing, and drying it at 250°C under nitrogen for 2 hours, thereby completing the three-layer nano-nickel cobalt gold deposition on the titanium ruthenium oxide support; the remaining steps are the same as in Example 1.

[0097] Effect example

[0098] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the methanol oxidation catalyst prepared in the following examples are as follows:

[0099] Activity test: Take 5 reduced methanol oxidation catalyst samples into a container, pass a mixed gas (4-4.5% carbon monoxide, 0.8-1.2% carbon dioxide, 50-60% hydrogen, and the rest nitrogen), control the pressure at 5.0MPa and the temperature at 25°C, measure the activity (expressed as the conversion rate of carbon monoxide), then subject the samples to a heat treatment at 400°C for 24h, and test the activity after heat resistance under the above conditions to indicate the thermal stability of the samples.

[0100] Table 1 below shows the performance analysis results of the methanol oxidation catalysts of Examples 1 to 3 of the present invention and Comparative Examples 1 to 10.

[0101] Table 1

[0102] CO conversion rate % CO conversion rate after heat resistance % Activity retention rate after heat resistance % Example 1 84.1 79.5 94.5 Example 2 82.5 77.9 94.4 Example 3 83.6 76.3 91.2 Comparative Example 1 62.7 44.1 70.3 Comparative Example 2 65.8 47.8 72.6 Comparative Example 3 72.4 49.4 68.2 Comparative Example 4 54.6 35.1 64.9 Comparative Example 5 55.8 40.5 72.6 Comparative Example 6 68.9 46.1 67.5 Comparative Example 7 70.1 41.4 59.1 Comparative Example 8 68.1 43.4 63.7 Comparative Example 9 59.4 34.7 58.4 Comparative Example 10 64.7 43.1 66.6

[0103] From the comparison of the data of the comparative example and the embodiment, it can be found that the present invention uses a low-temperature hydrothermal method to prepare nano titanium ruthenium oxide as a carrier, and the crystal phase of titanium ruthenium oxide is anatase structure, which synergizes with the deposited nickel, cobalt and manganese metals to improve the catalytic performance of methanol. The present invention first uses a silane coupling agent to surface-treat the titanium ruthenium oxide metal, and silanol reacts chemically with the surface hydroxyl groups of titanium ruthenium oxide to form a strong chemical bond, which can enhance the adhesion between the subsequently deposited metal nanoparticles and the carrier; and improves the stability of the catalyst at high temperatures, and reduces phase changes and structural changes during heat treatment; the formation of a modified layer changes the microenvironment of the nanoparticles, helps the metal nanoparticles reduce aggregation, evenly disperse, and improve their reaction activity and catalytic efficiency; and then immerses it in a homemade aqueous nano nickel solution to form a first layer of nano nickel metal layer, and then uses a silane coupling agent to surface-treat it again. The silanol groups can react chemically with the metal atoms on the surface of the nanoparticles to form stable chemical bonds, thereby forming an organic protective layer on the catalyst surface, which helps to control the nucleation and growth of the metal particles and prevent the excessive aggregation of the metal nanoparticles during the next impregnation process, thereby helping to maintain or improve the dispersion of the metal particles and prevent particle aggregation, thereby increasing the effective active surface area of ​​the catalyst and improving the catalytic efficiency; repeating the steps to deposit a second layer of nano-cobalt particles and a third layer of nano-manganese particles, and finally performing a reduction treatment to obtain a methanol oxidation catalyst with a nano-nickel, cobalt and manganese metal layer deposited on a titanium ruthenium oxide matrix.

[0104] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and no mark in the claims should be regarded as limiting the claims involved.

Claims

1. A method for preparing a methanol oxidation catalyst, characterized in that: The method comprises the following preparation steps: (1) Add ruthenium salt to a container, add deionized water to dissolve, then pour into a cup, add hydrogen peroxide while stirring, stir evenly, and cool in an ice bath; (2) adding the titanium compound to the solution, stirring evenly, then adding urea, stirring continuously, and cooling to room temperature; (3) placing the solution obtained in step (2) in a pressure cooker to carry out a high temperature and high pressure reaction, washing with water and centrifuging after the reaction is complete, and then vacuum drying to obtain a nano titanium ruthenium oxide carrier; (4) washing the nano-titanium ruthenium oxide carrier obtained in step (3), placing it in an oven, drying it under an inert gas, then adding a surface modifier to soak it, letting it stand, taking it out after the reaction is complete, washing it with deionized water and alcohol, drying it in an oven under an inert gas, cooling it to room temperature, placing it in a test tube filled with an inert gas, and refrigerating it in a refrigerator; (5) taking an aqueous solution of nano-nickel particles, placing the support after surface treatment in step (4) in the solution for immersion, taking it out for washing, and drying it under inert gas, thereby completing the deposition of a single layer of nano-nickel on the titanium ruthenium oxide support; (6) immersing the ruthenium oxide support on which the nano-nickel metal is deposited obtained in step (5) in a surface modifier, wetting it, and then placing it in an oven to dry it under an inert gas to complete the surface modification; (7) taking an aqueous solution of nano-cobalt particles, placing the titanium ruthenium oxide support obtained in step (6) in the solution for immersion, taking it out for washing, and drying it under inert gas, thereby completing the double-layer nano-nickel-cobalt deposition on the titanium ruthenium oxide support; (8) immersing the ruthenium oxide support on which the double-layer nano-nickel and cobalt are deposited obtained in step (7) in a surface modifier, wetting it, and then placing it in an oven to dry it under an inert gas to complete the surface modification; (9) taking an aqueous solution of nano-manganese particles, placing the titanium ruthenium oxide support obtained in step (8) in it for immersion, taking it out for washing, and drying it under inert gas, thereby completing the deposition of three layers of nano-nickel, cobalt and manganese on the titanium ruthenium oxide support; (10) placing the titanium ruthenium oxide support on which three layers of nano nickel, cobalt and manganese metals are deposited obtained in step (9) in a closed furnace, introducing a mixed gas, and heating the furnace for heat treatment to obtain a titanium ruthenium oxide methanol oxidation catalyst carrying nano nickel, cobalt and manganese metals after the reaction is complete; The surface modifier is 3-aminopropyltriethoxysilane-methanol solution with a concentration of 1% to 5%.

2. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The ruthenium salt is ruthenium chloride; and the metal titanium compound is tetraethyl titanium.

3. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The mass concentration of hydrogen peroxide in step (1) is 30% to 40%; the mass concentration of urea in step (2) is 0.3 to 0.7M.

4. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The ice bath temperature in step (1) is 0-5°C; the oven temperature in step (3) is 200-300°C, the time is 2-6 hours, and the heating rate is 5-15°C / min; the centrifugal speed in step (3) is 5000-6000 r / min.

5. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The inert gas is nitrogen; the drying temperature of steps (5), (7) and (9) is 200-300° C. and the drying time is 1-3 hours.

6. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The mixed gas in step (10) is 5% hydrogen and 95% argon; the reaction temperature is 550-650° C., the heating rate is 5-15° C. / min, and the reaction time is 4-8 hours.

7. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The aqueous nano nickel solution is prepared by the following steps: adding a nickel chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding a sodium borohydride aqueous solution, continuously stirring, cooling to room temperature, and obtaining aqueous nano nickel particles; the molar concentration of the nickel chloride is 0.5-5.0 mM, and the molar concentration of the sodium borohydride is 0.5-5.0 mM.

8. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The aqueous nano-cobalt solution is prepared by the following steps: adding a cobalt chloride aqueous solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding a sodium borohydride aqueous solution, continuously stirring, cooling to room temperature, and obtaining an aqueous nano-cobalt particle solution; the molar concentration of the cobalt chloride is 0.5-5.0 mM, and the molar concentration of the sodium borohydride is 0.5-5.0 mM.

9. The method for preparing a methanol oxidation catalyst according to claim 1, characterized in that: The aqueous nano-manganese solution is prepared by the following steps: adding an aqueous manganese chloride solution into a container, stirring evenly, heating the solution to boiling using a condensation reflux device, adding an aqueous sodium borohydride solution, continuously stirring, and cooling to room temperature to obtain an aqueous nano-manganese particle solution; the molar concentration of the manganese chloride is 0.5 to 5.0 mM, and the molar concentration of the sodium borohydride is 0.5 to 5.0 mM.

10. A methanol oxidation catalyst, characterized in that: The catalyst is prepared by the method described in any one of steps 1-9.

Citation Information

Patent Citations

  • Method for preparing aldehyde or ketone compounds with catalytic oxidation of alcohol compounds

    CN101293799A

  • Lithium ion battery anode composite material and manufacturing method thereof

    CN101527353A

  • Electrocatalyst for a fuel cell and the method of preparing thereof

    CN103456968A

  • Catalyst for purifying ammonia-containing tail gas in LED-MOCVD process, and preparation method and application of catalyst

    CN111167461A

  • Preparing method from sugar to sugar alcohols by catalytic hydrogenation

    KR1020120123189A